The Effectiveness Of Digital Media Mari Belajar On Human Movement System Material To Foster Curiosity Of Grade VI Elementary School Students - Anggraeni, Isnaeny Nurdiana; Utama, Candra; Winahyu, Sri Estu (Proceedings Series of Educational Studies, 2024)
This study aims to assess the effectiveness of digital learning media "Mari Belajar" in increasing the curiosity of grade VI elementary school students on the material of the human motion system. The method used was quantitative with a one-group pre-test and post-test experimental design, and saturated sampling technique involving 25 students. The research instruments included pre-test and post-test questionnaires and observation sheets. The results showed that this media was very valid with an Aiken index of 0.992188. The paired sample t-test produced a p-value of 0.00, which showed a significant difference before and after using the media. Observations showed a high level of student curiosity, with an average of 90% on the indicators of asking questions and actively seeking information, and 91% on enthusiasm. In conclusion, the "Mari Belajar" media proved effective in increasing students' curiosity, improving learning quality, and motivating students to learn more actively.